2017
DOI: 10.1080/23802359.2017.1419088
|View full text |Cite
|
Sign up to set email alerts
|

The complete chloroplast genome of an economic and ecological plant, paper mulberry (Broussonetia kazinoki × Broussonetia papyifera)

Abstract: (2018) The complete chloroplast genome of an economic and ecological plant, paper mulberry (Broussonetiakazinoki × Broussonetiapapyifera), Mitochondrial DNA Part B, 3:1, 28-29,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
(15 reference statements)
1
9
0
Order By: Relevance
“…Two genes ( ycf3 and clpP ) contained two introns. These two genes were similar to those in the Orpheus flower Haberlea rhodopensis and Broussonetia papyrifera (Ivanova et al, 2017; Xu et al, 2018). Unlike most angiosperm chloroplast genomes (Jin et al, 2014; Kong & Yang, 2015; Wang et al, 2016), among the 11 genes, four ( atpF , rpoC1 , ycf3 , clpP ) of which were located in the LSC region, two ( ndhA and trnI-GAU ) in the SSC region, other four ( rpl2 ×2, ndhB ×2) in the IR region, and one gene ( ycf1 ) was a trans-spliced gene with its start codon located in the SSC region, stop codon in the IRb region, and possibly missing 3′ end.…”
Section: Results and Analysissupporting
confidence: 58%
“…Two genes ( ycf3 and clpP ) contained two introns. These two genes were similar to those in the Orpheus flower Haberlea rhodopensis and Broussonetia papyrifera (Ivanova et al, 2017; Xu et al, 2018). Unlike most angiosperm chloroplast genomes (Jin et al, 2014; Kong & Yang, 2015; Wang et al, 2016), among the 11 genes, four ( atpF , rpoC1 , ycf3 , clpP ) of which were located in the LSC region, two ( ndhA and trnI-GAU ) in the SSC region, other four ( rpl2 ×2, ndhB ×2) in the IR region, and one gene ( ycf1 ) was a trans-spliced gene with its start codon located in the SSC region, stop codon in the IRb region, and possibly missing 3′ end.…”
Section: Results and Analysissupporting
confidence: 58%
“…And its maternal B. kazinoki has experienced controversy [15,54], therefore, it is necessary to compare ZJGS and its hybrid parent systematically. Unlike the previous study [36], the cp genome of ZJGS was analyzed in detail. Through comparison, it is found that the total length and total GC content of ZJGS cp genome sequence (160,903 bp and 35.74%, respectively) are closest to its maternal B. kazinoki (160,841 bp and 35.73%, respectively), while its paternal B. papyrifera is 160,239 bp and 35.83%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Our research group rst reported the complete cp genome of ZJGS and the sequence was submitted to Genebank with the accession number of MF496038. The more experiment details can be got from the announcement [36]. At the same time, 12 Moraceae plants, including six Broussonetia species and six Morus species were selected to compare cp genomes structure with ZJGS.…”
Section: Comparative Analyses Of Cp Genomes Structurementioning
confidence: 99%
See 1 more Smart Citation
“…In China, B. × kazinoki is highly valued not only for its fiber, but also as nonconventional forage, food additives, and traditional medicine, and its transcriptome (Xianjin et al, 2014) and chloroplast (cp) genome (Xu et al, 2018) has been studied.…”
mentioning
confidence: 99%